Clinical profile, conversion rate, and suicidal thinking and behaviour in children and adolescents at ultra-high risk for psychosis: a theoretical perspective - Maria Pontillo; Maria Cristina Tata; Roberto Averna; Prisca Gargiullo; Silvia Guerrera; Stefano Vicari (Research in Psychotherapy, 2020)
Over the past years there has been substantial growing interest in the prodromes of psychosis to identify individuals at risk for psychosis prior to their first psychotic episode. Researchers have proposed criteria to detect young adults at Ultra-High Risk (UHR) for psychosis, and these criteria have also been applied to children and adolescents, though few clinical studies have examined this population. This theoretical perspective presents some of the crucial issues in the assessment and treatment of UHR children and adolescents: the presence of a specific clinical profile (i.e., different to that of healthy controls and UHR young adults), the predictive value of UHR criteria, and the presence and clinical significance of suicidal thinking and behaviour. In UHR children and adolescents, like UHR young adults, the presence of Attenuated Psychotic Symptoms (APS) is the most frequently reported inclusion criterion at baseline, with a prevalence of approximately 89–100%. In addition, there are frequently non-psychotic comorbid diagnoses of depressive and anxiety disorders. In contrast to the UHR adult population, UHR children and adolescents demonstrate a lower conversion rate to frank psychosis, most likely due to their high rate of APS. Finally, UHR adolescents report a high prevalence of suicidal ideation and self-injurious behaviour (67.5%), as well as a significantly greater frequency of attempted suicide, relative to adolescents with frank psychosis. On this basis, UHR children and adolescents report a clinical complexity that should be carefully monitored and considered for specific and targeted therapeutic interventions to be planned and developed